2008
DOI: 10.1507/endocrj.k07e-032
|View full text |Cite
|
Sign up to set email alerts
|

Combination of C-reactive Protein and High Molecular Weight (HMW)-Adiponectin Reflects Further Metabolic Abnormalities Compared with Each of Them Alone in Japanese Type 2 Diabetic Subjects

Abstract: Abstract. Objective: Serum C-reactive protein (CRP) and adiponectin levels predict atherosclerosis and coronary heart disease. However, the efficacy of the combination of both markers remains unknown. In the present study, we investigated whether the combination of CRP and adiponectin is associated with further metabolic abnormalities compared to each of them alone. Research design and methods: Eighty-three Japanese type 2 diabetic outpatients participated in this study. We measured serum high-sensitive CRP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Adiponectin and CRP are independent risk factors of CVD, together serve a synergistic role in metabolic regulation in the general population and T2D subjects [35][36][37] . We found that AA women with high adiponectin and low CRP levels, which translated into a high ratio, had significantly lower FG, IN, HOMA-IR, WC, %BF and BMI relative to those with a low ratio.…”
Section: Comparedmentioning
confidence: 99%
“…Adiponectin and CRP are independent risk factors of CVD, together serve a synergistic role in metabolic regulation in the general population and T2D subjects [35][36][37] . We found that AA women with high adiponectin and low CRP levels, which translated into a high ratio, had significantly lower FG, IN, HOMA-IR, WC, %BF and BMI relative to those with a low ratio.…”
Section: Comparedmentioning
confidence: 99%
“…Recently, Tabara et al have shown synergistic effects of CRP and HMW adiponectin on metabolic abnormalities in older Japanese subjects 24) , which indicate the superiority of a combination of both markers. We have also reported the synergistic effects of both markers on metabolic abnormalities in Japanese type 2 diabetic subjects 25) ; however, these studies did not measure waist circumference to evaluate MetS. In contrast, Devaraj et al have reported a comparison among CRP, HMW adiponectin and its ratio in the evaluation of MetS in 123 subjects with MetS and 91 subjects without MetS 26) .…”
Section: Discussionmentioning
confidence: 96%
“…Establishing a robust biomarker that can predict MetS instead of examining individual features will be important to screen populations of individuals, monitor the natural history of the disease, and measure the response to therapeutic interventions. We and others have shown a synergistic effect of CRP and HMW adiponectin to evaluate MetS in the general population 24) and type 2 diabetic subjects 25) , suggesting a superior effect when both markers are combined. In contrast, Devaraj et al have reported that CRP, HMW adiponectin and its ratio were comparable to predict MetS 26) .…”
mentioning
confidence: 77%
See 2 more Smart Citations